THE EFFECT OF THE INDONESIAN NATIONAL POLICE'S PRESISI MOBILE APPLICATION ON THE QUALITY OF PUBLIC SERVICES - Ismail, Muhammad Hady Kusuma; Ari Sulistyanto; Wichitra Yasya (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to determine the effect of the Indonesian National Police's PRESISI Mobile Application on the Quality of Public Services. Data collection was done using primary data obtained from distributing questionnaires through Google Forms. The population in this study is probabilistic and cannot be determined precisely, but the sample calculation used the Lemeshow formula, resulting in 96 people rounded up to 100 respondents. This research is quantitative, and the data obtained were analyzed using simple linear regression analysis processed using SPSS version 24. Based on the analysis results, the variable of the Indonesian National Police's PRESISI Mobile Application has a significant partial effect on the Quality of Public Services. This study was able to demonstrate that the PRESISI Mobile Application of the Indonesian National Police has a 44.9% effect on the Quality of Public Services, while the remaining 55.1% is affected by other unobserved factors not included in this study. These results suggest that the PRESISI Mobile Application of the Indonesian National Police is an important factor in technological development for improving the quality of mobile-based public services that are easily accessible to the public for receiving services or information related to the police